2023
DOI: 10.3126/ije.v12i1.52439
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration Status and Population Structure in Terai Community Forest: Evidence from Kalyankot Community Forest, Kapilvastu District, Nepal

Abstract: The regeneration status of a forest is an essential metrics to assess the regeneration potential and population structure of forests. In emerging nations like Nepal, however, human dependency on forests has had a negative influence on forest diversity and sustainability. This paper analyzes the regeneration status and its link with bio-physical aspects and human disturbances. The data were collected using a systematic random sampling method and sample plots were established using the fishnet tool in ArcGIS. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…Dhungana & Chhetri followed by the upper elevation stratum and inconsiderable in the lower elevation stratum which corresponds with the findings of Kharal et al (2015). Likewise, Chhetri et al (2023) found the forest in a good regeneration condition in the tropical region of Nepal, but our study found the seedling condition of T. dumosa species in 'medium' condition in the lower and middle elevation strata, while it was in a 'poor' state in the upper elevation stratum. On the other hand, the seedling condition of A. spectabilis, as per the CF Inventory Guidelines ( 2004), was deemed to be in a 'poor' state in all the three elevation strata.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Dhungana & Chhetri followed by the upper elevation stratum and inconsiderable in the lower elevation stratum which corresponds with the findings of Kharal et al (2015). Likewise, Chhetri et al (2023) found the forest in a good regeneration condition in the tropical region of Nepal, but our study found the seedling condition of T. dumosa species in 'medium' condition in the lower and middle elevation strata, while it was in a 'poor' state in the upper elevation stratum. On the other hand, the seedling condition of A. spectabilis, as per the CF Inventory Guidelines ( 2004), was deemed to be in a 'poor' state in all the three elevation strata.…”
Section: Discussionsupporting
confidence: 87%
“…Anthropogenic disturbances like grazing, logging, and fuelwood collection are identified as major contributors to forest degradation in Himalayan ecosystems (Maren & Sharma, 2018). Most of the population structure and regeneration studies are reported from the Terai forests of Nepal (Chhetri et al, 2023). However, there remains a significant gap in understanding the regeneration dynamics of the forests across the elevation gradient in the Nepal Himalaya (Kharal et al, 2015).…”
mentioning
confidence: 99%